ЭКСПЕРИМЕНТАЛЬНЫЕ ИССЛЕДОВАНИЯ ПРЕОБРАЗОВАНИЯ ДАННЫХ СКОЛЬЗЯЩИМИ УПОРЯДОЧЕННЫМИ ВЫБОРКАМИ - Мазманян, Р.О. (Інститут електродинаміки НАН України, Київ, 2012)
The article describes median filters of improbable data experimental studies, their numerical characteristics, correlation functions as well as spectral characteristics of ordered samples of a given range of uncorrelated random signal with zero mean. Experimental results are specified as characteristics of the samples expressed both according to the formulas derived from theoretical studies as well as obtained by numerical imitational modeling by reviewed data processing method. To assess the statistical proximity of the results a graphical representation of the experimental data is used. References 7, figures 10.